Influences of cultural values, community cohesiveness, and resilience among residents in insurgency-prone Northeast Nigeria - Butu, Hauwa Mai; Hashim, Ahmad Hariza; Ahmad, Nobaya; Hassan, Mohammad Mujaheed (Human Resource Management Academic Research Society, 2023)
The concepts of risk and resilience have gained growing relevance in the context of cultural values and community cohesiveness. Specifically, in the face of threat particularly in situations like armed conflicts. Simultaneously, there is an argument that emphasizes, cultural values and community cohesiveness are valuable assets for fostering resilience, lessening disaster risk, and promoting peace and reconciliation among individuals in many communities around the globe. The current study seeks to understand whether cultural values and community cohesiveness influence resilience among affected public housing residents in Maiduguri Borno State Nigeria. Hofstede cultural value model, was used as the model for this study. The study employed a cross-sectional design, used questionnaire for data collection, and a sample size of 345 across 5 public housing, based on the proportion of their population, using Cochran (1977), formula in determining the sample size. Data was analysed using SPSS package version 25. The descriptive analysis, reveals a high level of cultural values and community cohesiveness while results from the regression analysis indicate that cultural values and community cohesiveness predict resilience. The study therefore suggests that culture should be cooperated in neighbourhood and housing design. Likewise, coping strategies such as resilience-oriented planning to deal with the security situation at all levels should pay special attention and support community social networks in order to enhance their resiliency.